2020
DOI: 10.1093/jn/nxz255
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a Bioactive Oil Enriched in Stearidonic Acid during Early Life Influences Immune System Maturation in Neonatal Sprague-Dawley Rats

Abstract: Background Long-chain n–3 PUFAs (LCPUFAs) improve immune development and reduce atopic disease risk in infants. Stearidonic acid (SDA) can be a substrate for biosynthesis of n–3 LCPUFAs. Objective We aimed to determine the effect of feeding an SDA-enriched diet during suckling and weaning on offspring immunity and ability to develop oral tolerance (OT). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Similarly, EPA-enriched phospholipids have been found to reduce LPS-induced increases in the level of IL-1β in the hippocampus, thalamus, and cortex [67]. A recent study has shown that pups exposed to a maternal diet enriched with stearidonic acid (SDA) that increased total VLC n-3 PUFAs (EPA, DPA, and DHA) exhibited less inflammatory IL-6 and TNF-α in response to LPS than the control group [68].…”
Section: Effect Of Vlc N-3 Pufas On Neuroinflammationmentioning
confidence: 99%
“…Similarly, EPA-enriched phospholipids have been found to reduce LPS-induced increases in the level of IL-1β in the hippocampus, thalamus, and cortex [67]. A recent study has shown that pups exposed to a maternal diet enriched with stearidonic acid (SDA) that increased total VLC n-3 PUFAs (EPA, DPA, and DHA) exhibited less inflammatory IL-6 and TNF-α in response to LPS than the control group [68].…”
Section: Effect Of Vlc N-3 Pufas On Neuroinflammationmentioning
confidence: 99%
“…Remarkably, avonoids and anthocyanins have signi cant anti-lipid peroxidation and anti-oxygen free Procyanidin B2 involved in numerous hypoxia-related disease, and triggered expressions of genes involved in immunity and related diseases. Stearidonic acid could promote immunity through activating p38 MAP kinase activity and CD4 + T cell, while Arachidonic acid could control macrophage alternative activation through regulating oxidative phosphorylation in PPARγ to improve immunity(Xu et al, 2021;Patel et al, 2020;Nandakumar et al, 2008). Thus, the accumulation of avonoid and anthocyanins could promote the medicinal value of Polygonum viviparum L. in improving diseases associated with high altitude, such as hypoxia and UV exposure.In our present study, we revealed the adaptive mechanism of Polygonum viviparum L. to increase of altitude through altering metabolic compositions, especially fatty acids and avonoids, for guaranteeing normal growth and promoting medicinal value of Polygonum viviparum L..…”
mentioning
confidence: 99%